Association of the polymorphisms in FOXO1 gene and diabetic nephropathy risk - Ma, Jianxia; Pei, Yongbin; Xue, Peng; Wang, Yan; Bao, Xiaoxue; Li, Yukun (Artificial cells, nanomedicine, and biotechnology, 2019)
This study was aimed to study the hypothesis that forkhead box O1 (FOXO1) gene rs17446614 and rs17592236 single nucleotide polymorphisms (SNPs) influenced the development of diabetic nephropathy (DN). This study included 138 DN patients and 149 healthy controls. Controls were matched with the patients in age and gender. The method of polymerase chain reaction-restriction fragment length polymorphisms (PCR-RFLP) was used to detect FOXO1 gene polymorphisms. Haploview software was conducted to analyze the linkage disequilibrium and haplotypes of FOXO1 gene polymorphisms. Relative risk of DN was expressed by odds ratios (ORs) and 95% confidence intervals (95% CIs), then the results were adjusted by clinical characteristics of the study subjects using logistic regression analysis. Subgroup analysis was performed according to gender. AA genotype of rs17446614 SNPs was significantly associated with the risk of DN (P = .037, adjusted OR = 5.412, 95% CI = 1.103-26.559), especially in female (OR = 8.700, 95% CI = 1.008-75.062, P = .021). FOXO1 rs17446614 A allele positively associated with the development of DN (P = .027, adjusted OR = 1.680, 95% CI = 1.060-2.662), particularly in women (OR = 2.003, 95% CI = 1.070-3.749, P = .028). A-C haplotype formed by FOXO1 gene rs17446614 and rs17592236 SNPs was significantly associated with the increased risk of DN (P = .011, OR = 1.850, 95% CI = 1.146-2.986). FOXO1 gene rs17446614 SNP, and the A-C haplotype of rs17446614 and rs17592236 polymorphisms were risk factors for the development of DN.